Cytotoxic and antioxidant effects of grape seed oil on the treatment of leukemia with methotrexate - Sahin, Nefise Ozlen; Berkoz, Mehmet; Eker, Ebru Derici; Pomierny, Bartosz; Przejczowska, Katarzyna (European Journal of Chemistry, 2012)
Methotrexate (MTX), a widely used cytotoxic chemotherapeutic agent, is often limited by its severe toxicity. Regarding the mechanisms of its adverse effects, several hypotheses have been put forward, among which oxidative stress is highly noticeable. Additive effect of oxidative damage caused by MTX to oxidative stress induced by cancer makes the situation dramatically bad. In order to reduce the damage, several approaches have been suggested. Grape seed is one of the most significant prophylactic agents due to its antioxidant and bioflavonoids composition. The aim of this study was to investigate the protective effect of grape seed oil against MTX-induced oxidative stress in K-562 human chronic myeloid leukemia cell lines. Cells were divided into groups as following control, GSOH (tumor cells treated with 200 mg/mL of grape seed oil), GSOL (tumor cells treated with 100 mg/mL of grape seed oil), MTX (tumor cells treated with 50 nM methotrexate) and MTX + GSOH ( tumor cells treated with 200 mg/mL of grape seed oil and methotrexate). For antioxidant statue; superoxide dismutase (SOD), catalase (CAT), paraoxonase (PON) and aryl esterase (ARE) activities, for lipid peroxidation; malondialdehyde (MDA) level and also for cytotoxicity; cell viability were detected in 24th and 48th hours of the cell culture incubation. Based on the data, 200 mg/mL of grape seed oil indicates synergic effects with MTX on K562 regarding cytotoxicity especially in 48th hour. In case of GSOH + MTX combined treatment for 24 hours, antioxidant system take part preventing lipid peroxidation and a possible oxidative damage. Upon 48 hour-GSOH treatment, antioxidant parameters show significant increase and hence, prevent lipid peroxidation in cancer cells. In conclusion, GSOH complimentary treatment may be suggested for leukemia therapy with MTX to reduce side effects and enhance the cytotoxicity of MTX.